2008
DOI: 10.1016/j.jcp.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of unsteady sampling procedures for the parallel direct simulation Monte Carlo method

Abstract: Simulations are then conducted of two applications involving the interaction of shocks over wedges. The results of these simulations are compared to experimental data and simulations from the literature where there these are available. In general it was found that ten ensembled runs of DREAM processing could reduce the statistical uncertainty in the raw PDSC data by 2.5-3.3 times, based on the limited number of cases in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The injection of a small volume of liquid precursor solution with ultrasonic atomization produces a sharp pressure pulse in the reactor followed by pump‐down to the base pressure between each cycle. The non‐steady injection process results in a well‐mixed reactor condition, as shown by numerical modeling and experimentation in our previous research 32–35. As the reactor is pumped down, the remaining precursor is consumed on the substrate.…”
Section: Analysis Methodsmentioning
confidence: 89%
“…The injection of a small volume of liquid precursor solution with ultrasonic atomization produces a sharp pressure pulse in the reactor followed by pump‐down to the base pressure between each cycle. The non‐steady injection process results in a well‐mixed reactor condition, as shown by numerical modeling and experimentation in our previous research 32–35. As the reactor is pumped down, the remaining precursor is consumed on the substrate.…”
Section: Analysis Methodsmentioning
confidence: 89%
“…The DSMC code, PDSC++, is a general-purpose parallel 2D/2D-axisymmetric/3D DSMC code using unstructured grid, which is developed by Wu's group. Some important features of the PDSC++ include hybrid unstructured mesh, variable time-step scheme (Wu, Tseng & Wu 2004), transient adaptive sub-cell method (Su et al 2010), unsteady simulation (Cave et al 2008), domain redecomposition, automatic steady state detection scheme, parallel computing technique and chemical reaction based on total collision energy model (Lo et al 2015). It also has been applied to the rare gas flows of cometary comas (Finklenburg et al 2014;Lai et al 2016;Marschall et al 2016).…”
Section: The Solar Illumination Effectmentioning
confidence: 99%
“…All of the previous experience with PP-MOCVD has been carried out in a research-scale vertical tube, cold wall reactor with volume 1.67 L that could coat samples up to 2 cm 2 . Numerical modelling studies have shown that the unique expansion-driven mass transport regime could be scaled up and that different chamber geometries could be used [3,4]. The research objective for this project was to demonstrate the design relations for scale-up and the capability of the PP-MOCVD method to coat a complex object.…”
Section: Introductionmentioning
confidence: 99%